2023
DOI: 10.3390/horticulturae9020144
|View full text |Cite
|
Sign up to set email alerts
|

Two New Ferula (Apiaceae) Species from Central Anatolia: Ferula turcica and Ferula latialata

Abstract: Ferula turcica and Ferula latialata are two novel endemic species discovered in the Konya and Kırşehir provinces of the central Anatolian region of Türkiye. These two new species are described by morphological, ecological, carpological, and phytochemical characteristics and phylogenetic analysis. F. turcica and F. latialata are morphologically distinct from F. szowitsiana by their habit, the stalk of the terminal umbella, and the mericarp size, as well as by the profile of their secondary metabolite markers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Six new sesquiterpene coumarin ethers, namely turcicanol A (1), turcicanol A acetate (2), turcicanol B (3), turcica ketone (4), 11 -dehydrokaratavicinol (5), and galbanaldehyde (6), and a new sulfur-containing compound, namely turcicasulphide (7), were isolated from the dichloromethane extract of the roots of Ferula turcica (Figure 1). Turcicanol (1) was isolated as an amorphous white powder.…”
Section: Characterization Of Cytotoxic Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six new sesquiterpene coumarin ethers, namely turcicanol A (1), turcicanol A acetate (2), turcicanol B (3), turcica ketone (4), 11 -dehydrokaratavicinol (5), and galbanaldehyde (6), and a new sulfur-containing compound, namely turcicasulphide (7), were isolated from the dichloromethane extract of the roots of Ferula turcica (Figure 1). Turcicanol (1) was isolated as an amorphous white powder.…”
Section: Characterization Of Cytotoxic Compoundsmentioning
confidence: 99%
“…When the cytotoxic activity results of the pure compound turcica ketone (4), an isomer of badrakemone (12) and mogoltadone (22), were examined, the endocyclic double bond was more cytotoxic than the exocyclic double bond, as in badrakemone (12) and mogoltadone (22). The cytotoxic activity results of galbanic acid (27) and its aldehyde derivative (6) showed that the aldehyde form of C-3 increased the cytotoxic activity on HCT116 colon cancer cell lines.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Boissier classified the genus Ferula species grown in the Iran-Turanian region into three sections based on the shape of their petals and the number of their vittae: Peucedanoides Boiss. Scrodosma Bunge and Euferula Boiss [12] [13] [14]. 106 species are found in the CIS countries, 105 species in Central Asia, 63 species in Uzbekistan, more than 50 species in Western Tyan-Shan, about 60 species in the Pamir-Alai range, and 33 species in the western Pamir-Alai range [10].…”
Section: Introductionmentioning
confidence: 99%